A General Approach for Fast Detection of Charge Carrier Type and Conductivity Difference in Nanoscale Materials. (7th October 2013) - Jiang, Lili; Wu, Bin; Liu, Hongtao; Huang, Yuan; Chen, Jianyi; Geng, Dechao; Gao, Hongjun; Liu, Yunqi
<x xml:space="preserve">Abstract</x> A general method using a biased atomic force microscopy tip that allows a qualitative, fast, and reliable determination of key electronic properties such as metallic, n‐, or p‐doped characteristics has been reported for the first time. This method eliminates the detrimental effect of contact in the traditional transport measurement and is much simpler than the common‐electrostatic force microscopy detection method, thus providing a powerful tool for fast characterizations of nanomaterials. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>